2009
DOI: 10.1039/b903772a
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism of nitrobenzospiropyran in phosphonium based ionic liquids

Abstract: The photo-, thermo-and solvatochromic properties of 2,3-dihydro-1 0 ,3 0 ,3 0 -trimethyl-6-nitrospiro[1-benzopyran-2,2 0 -1H-indole] (BSP) and its photo-induced merocyanine isomer (MC)were investigated in phosphonium based ILs by UV-vis absorption spectroscopy. It was found that the kinetics and thermodynamics of the BSP 2 MC equilibrium were sensitive to the nature of the anion. The MC l max shifted from 560 nm to 578 nm when in solutions of [P 1,4,4,4 ][tos] and [P 6,6,6,14

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…It was found that the spectroscopic data obtained in phosphonium ILs contradicted what was expected for benzospiropyran in molecular solvents, with the evidence suggesting that the probe molecule was experiencing multiple solvation shells. [23] Within the IL field, phosphonium-based ILs possess some interesting and often advantageous properties. When compared with the popular imidazolium based ILs, phosphonium cations lack the acidic proton which leads to carbene formation, [24] and are often less dense than water when compared to nitrogen based ILs.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the spectroscopic data obtained in phosphonium ILs contradicted what was expected for benzospiropyran in molecular solvents, with the evidence suggesting that the probe molecule was experiencing multiple solvation shells. [23] Within the IL field, phosphonium-based ILs possess some interesting and often advantageous properties. When compared with the popular imidazolium based ILs, phosphonium cations lack the acidic proton which leads to carbene formation, [24] and are often less dense than water when compared to nitrogen based ILs.…”
Section: Introductionmentioning
confidence: 99%
“…23 Based on this property, the MC isomer in solution has been studied for its potential use as an empirical indicator of solvent polarity of typical organic solvents 24,25 , aqueous binary solvent mixtures 26 and even ionic liquids. 27,28 Monolayers of spiropyran derivatives have been also bound to glass slides to study the polarity of their microenvironment 29 . Although this approach offers interesting information about the interaction…”
Section: Scheme 1 Photochromic Behaviour Of Monomeric Spiropyransmentioning
confidence: 99%
“…16,17,22 Recently, the well-known photo-, thermo-and solvato-chromic properties of benzospiropyran (BSP) and spirooxazine derivatives have been used by our group to provide new insights into the nanostructure of ILs through in situ mediation of their switching behaviour. 16,17 Furthermore the presence of the phenolate anion in the MC isomer provides a weak binding capacity for certain metal ions (d-and f-elements), and the resulting complexes generate new absorbance bands in the visible region, which are directly influenced by the type of metal ion present.…”
Section: Introductionmentioning
confidence: 99%
“…16,17,22 Recently, the well-known photo-, thermo-and solvato-chromic properties of benzospiropyran (BSP) and spirooxazine derivatives have been used by our group to provide new insights into the nanostructure of ILs through in situ mediation of their switching behaviour. 16,17 Furthermore the presence of the phenolate anion in the MC isomer provides a weak binding capacity for certain metal ions (d-and f-elements), and the resulting complexes generate new absorbance bands in the visible region, which are directly influenced by the type of metal ion present. [18][19][20][21] Polythiophenes (PThs) are a class of organic polymeric semiconductors with extremely interesting conductivity, electrochromism and electroluminescence 23 properties, which have been explored for applications such as electrochemical sensors and energy harvesting devices.…”
Section: Introductionmentioning
confidence: 99%